Valoración de la prueba biológica del adn indirectamente obtenida frente a la objeción de conciencia - Chamba Díaz, Wilson Orlando (2017)
The DNA testing is one of the means of scientific test with more truth today. In the investigation of crimes, brings boundless importance, contributing greatly to clarify the crimes, perpetrators and accomplices. For that reason, the Ecuadorian law must accept the indirect collection of such evidence when you do not have the consent of the person involved and it does not mean it is a violation of his fundamental rights how to the conscientious objection, the privacy or the integrity. The object of this research proves the importance of an amendment to the criminal law and thus to contribute to the techniques and research activities.